Data Fusion in Wireless Communication Network Node Positioning - Luo, Ya; Liu, Xiaoyang; Liu, Chao (Discoveries in Agriculture and Food Sciences, 2019)
Aiming at the problems of low localization accuracy, high energy consumption and delay of transmission in wireless sensor networks, a wireless sensor network data fusion method is proposed. Combined with the theory of D-S argument, the wireless sensor network system model is first constructed. Then based on the analysis of ACO (Ant Colony Optimization) and MST (Minimum Spanning Tree) methods, a wireless sensor network data fusion method is proposed. The simulation results show that the larger the number of nodes in WSN is, the larger the energy consumption and delay are. As the moving speed of Sink node increases, the average transmission delay decreases and the useful data rate increases. The average energy The consumption is also gradually increasing; the performance of proposed WSN data fusion method is better than that of ACO and MST.